2000
DOI: 10.1097/00003246-200006000-00070
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol delivery by metered-dose inhaler in a pediatric high-frequency oscillatory ventilation model

Abstract: These in vitro results suggest albuterol delivery by MDI in a pediatric model of HFOV is negligible, regardless of the operating frequency, inspiratory time, or use of a spacer or actuator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…The results are consisted with other experimental and numerical studies who concluded that particle deposition in a lung model would be higher under HFOV (Alzahrani 2010) and that application of HFOV would force particles to deposit on the endotrachial tube of a pressurized meter dose inhaler medical device on an overwhelming percentage (Garner et al 2000).…”
Section: Comparisonsupporting
confidence: 60%
See 1 more Smart Citation
“…The results are consisted with other experimental and numerical studies who concluded that particle deposition in a lung model would be higher under HFOV (Alzahrani 2010) and that application of HFOV would force particles to deposit on the endotrachial tube of a pressurized meter dose inhaler medical device on an overwhelming percentage (Garner et al 2000).…”
Section: Comparisonsupporting
confidence: 60%
“…Different carrier gases and different oscillating frequencies were used and the conclusion was that particle transport was faster in gases of higher kinematic viscosity and particle deposition is expected to increase with the oscillating frequency at high frequency situations (>2 Hz). Garner et al (2000) examined albuterol transfer by metered-dose inhaler in a high-frequency oscillatory ventilation model and concluded that albuterol transfer under that model would be problematic due to the high particle deposition on the endotracheal tube of the setup. Alzahrani (2010) compared albuterol delivery under HFOV, and CV by using an experimental setup with a pressurized meter dose inhaler (pMDI) and an adult cast lung model with different compliance levels.…”
Section: Particle Transport and Deposition Through Hfovmentioning
confidence: 99%
“…Very few studies have evaluated aerosol delivery during HFOV. Using a pressurized metered-dose inhaler with the holding chamber placed at the airway, Garner et al 22 reported negligible delivery of albuterol to a filter placed distal to the ETT. In contrast, Alzahrani et al 26 demonstrated that albuterol delivery during HFOV was significantly greater than that during conventional ventilation using an adult cast model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many clinicians are hesitant to administer aerosolized drugs during HFOV on the basis of a previous report that medication delivery to infants is negligible due to the small volumes, short inspiratory times, and high gas flows used with this form of ventilation. 22 We designed this in vitro study to quantify aerosol drug delivery with the hypothesis that effective levels of aerosol drug delivery could be achieved during both conventional ventilation and HFOV and that deposition efficiency would be different using a vibrating-mesh nebulizer (VMN) between each ventilator type and at two different circuit locations.…”
mentioning
confidence: 99%
“…There are relatively little published data on the efficacy and best techniques for the delivery of aerosol drugs during HFOV. Use of a metered-dose inhaler and spacer placed between the endotracheal tube and Y-connection resulted in negligible (Ͻ1%) drug delivery to a filter placed at the endotracheal tube tip (47). Use of conventional flow-driven nebulizers in the HFOV circuit will result in alterations of mPaw and ⌬P that require clinician readjustment of these variables to maintain baseline settings.…”
Section: Changes In Displayed Hfov Variables In Response To Changing mentioning
confidence: 99%